General Synthetic Strategy to Ordered Mesoporous Carbon Catalysts with Single‐Atom Metal Sites for Electrochemical CO2 Reduction (Small 16/2022). Issue 16 (21st April 2022) - Luo, Zhicheng; Yin, Zhouyang; Yu, Jiaqi; Yan, Yu; Hu, Bing; Nie, Renfeng; Kolln, Anna F.; Wu, Xun; Behera, Ranjan K; Chen, Minda; Zhou, Lin; Liu, Fudong; et al.
Abstract : CO2 Reduction In article number 2107799, Wenyu Huang, Sen Zhang, Long Qi, and co‐workers achieve a benchmark study of various single‐atom transition metal catalysts for electrochemical reduction of CO2 to CO. The single‐atom Ni anchored on ordered mesoporous nitrogen assembly carbon catalyst, Ni‐NAC, possesses not only high CO selectivity and current density, but also high durability in a broad potential range.